A LEGAL PERSPECTIVES OF THE MALAYSIAN AND INTERNATIONAL LAW IN COMBATING DOMESTIC VIOLENCE CASES DURING PANDEMIC COVID-19 - Siti Farrah Shahwir,; Noraini Ismail,; Rahmawati Mohd Yusoff,; Wan Amir Azlan Wan Haniff,; Zulhazmi Yusof,; Alizah Ali, (Journal of Islamic, Social, Economics and Development, 2023)
The Covid-19 pandemic has a significant likelihood of intensifying domestic violence. This paper examines the current legal framework for women's protection of their social rights against domestic violence based on Malaysian and international law. The analysis is based on a qualitative and descriptive cross-sectional analysis of the governing statutes, reported cases, and data gathered from the administrative authorities. The issue is also examined from the perspective of the Qur'an and the Sunnah. The research concludes that the Domestic Violence Act 1994 and Penal Code serve as the primary legal framework for dealing with domestic violence cases. However, although various international legal instruments are in place, when it comes to implementation, it remains unclear whether such facilities are being fully utilised in individual communities or not. Therefore, this issue needs to be addressed. It is proposed that the principle rights of women as outlined in the Islamic law must be strengthened in the government policies as the impact is in line with the Sustainable Development Goals (SDG) Plan (2030) in terms of gender equality, promoting peace from any violence and inclusive societies as well as communities for sustainable environment and development.